2015
DOI: 10.3109/08941939.2014.998798
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Investigation of the Analgesic Effects of Metamizole and Paracetamol in Rats

Abstract: Our results show that metamizole is more effective than paracetamol for treating surgical trauma-related pain, inflammation, and oxidative stress and hence may be a preferential drug to paracetamol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…However, no correlation between paclitaxel-induced neuropathic pain and MDA, MPO and tGSH levels has been reported in the literature. It has been reported elsewhere that MDA levels increased proportionally in relation to a decrease in the paw pain threshold (20), while Cetin et al (25) observed that MDA decreased in paw tissue with a corresponding increase in pain threshold. In another study, MDA was shown to increase in the presence of neuropathic pain (26).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, no correlation between paclitaxel-induced neuropathic pain and MDA, MPO and tGSH levels has been reported in the literature. It has been reported elsewhere that MDA levels increased proportionally in relation to a decrease in the paw pain threshold (20), while Cetin et al (25) observed that MDA decreased in paw tissue with a corresponding increase in pain threshold. In another study, MDA was shown to increase in the presence of neuropathic pain (26).…”
Section: Discussionmentioning
confidence: 98%
“…Analgesic activity (%)=100−[(100×paw pain threshold measured on day 7 after the administration of paclitaxel (g)/paw pain threshold measured after the administration of anakinra (g)] (20).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the amount of MDA has been reported to be elevated both in inflammatory and noninflammatory pains; this suggests that oxidative stress has a role in pain pathogenesis [ 33 ]. Ilker et al stated the importance of oxidative stress in the pathogenesis of incision-related postoperative pain and reported that MPO gene expression increased in damaged tissue that underwent incision; in addition, they demonstrated that metamizol, which significantly inhibited the increase of MPO gene expression, had a more potent analgesic effect than paracetamol, which could not inhibit MPO expression [ 15 ]. SF mucus and DS inhibited increase of MPO activity in the paw as a result of incision, and this suggests that inhibition of the increase of MPO activity is one of the significant analgesic activity mechanisms of SF.…”
Section: Discussionmentioning
confidence: 99%
“…Malondialdehyde (MDA), myeloperoxidase (MPO), nitric oxide (NO), total reduced glutathione (tGSH), superoxide dismutase (SOD), and COX-2 gene expression parameters were measured in the extracted paw tissues. Analgesic activity was calculated by the method of Ince et al [ 15 ]. All results obtained from the experiment were evaluated in comparison with the SIC group (n=6).…”
Section: Experimental Groupsmentioning
confidence: 99%
See 1 more Smart Citation